PENGAMANAN AKSES LAPORAN KEUANGAN UMKM MENGGUNAKAN QR CODE TERENKRIPSI DAN MULTI-FACTOR AUTHENTICATION - Riduwan, Riduwan; Hidayasari, Nurmi; Ikhsan Wibowo, Muhammad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The web-based financial recording and reporting system for Micro, Small, and Medium Enterprises is a digital solution designed to assist business actors in managing financial transactions in a structured, safe, and efficient manner, including recording income, expenses, business capital, and operational expenses, and generating automated financial reports. The development of this system uses the Waterfall method which includes the stages of analysis, design, implementation, testing, and deployment. The system is equipped with a security mechanism in the form of Quick Response Code authentication and PIN verification to improve access protection to accounts and financial statements. The results of the study show that the system is able to generate financial reports accurately, as well as implement effective security controls based on Black Box testing. Thus, the implementation of a Quick Response Code-based login and report access mechanism has been proven to be able to increase the security and ease of access to financial statements for Micro, Small, and Medium Enterprises without requiring business owners to log in directly to the system.